Fire-resistant building wire and cable and preparation method thereof
By using technical means such as combined wire cores and modified magnesium hydroxide in wire and cables, the problem of existing wire and cables being prone to melting and casting fire during combustion is solved, and higher flame retardant, waterproof and mechanical damage resistance are achieved, meeting the requirements of building fire safety.
Patent Information
- Application Number
- CN202411001689.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-25
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-07-25
AI Technical Summary
The sheathing materials of existing wires and cables are prone to melting and casting fire during combustion, which cannot meet the flame retardant and fire resistance requirements of building fire hazards.
The cable core is composed of multiple combined wire cores, mica belt layers and alkali-free glass fibers, and modified magnesium hydroxide and self-healing elastomers are used in the outer sheath to form flame retardant, waterproof, and mechanical damage-resistant wires and cables.
It improves the impact resistance, spray resistance, high temperature resistance and ablation resistance of wires and cables, meets the flame retardant and fire resistance requirements of building fire safety, and extends the service life of the cable.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electric wires and cables, in particular to a fire-resistant electric wire and cable for construction and a preparation method thereof. Background Art
[0002] In modern society, wires and cables are widely used in many fields of the national economy, playing the role of transmitting information and realizing electromagnetic energy conversion, making significant contributions to social development. With the advancement of urbanization, fire safety of various buildings has always been a focus of attention. Therefore, wires and cables used in various buildings need to have certain flame retardant and fire-resistant properties to eliminate fire hazards in buildings.
[0003] The sheath materials of existing wires and cables are mostly made of polyolefin materials with good electrical insulation and weather resistance, such as polyethylene, polypropylene and their copolymers. However, most polyolefin materials are prone to melting dripping and casting fire during combustion, and cannot meet the flame retardant and fire resistance level requirements of wire and cable fire safety. Flame retardants are generally added to modify the sheath material to make it flame retardant, and there are also problems such as poor compatibility with the sheath base material. Summary of the invention
[0004] The object of the present invention is to provide a fire-resistant building wire and cable and a preparation method thereof, so as to solve the problems in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A fire-resistant building wire and cable, comprising a cable core, a reinforcement layer wrapped on the surface of the cable core, and an outer sheath; the cable core is composed of a plurality of combined wire cores, a mica tape layer wrapped on the plurality of combined wire cores, and alkali-free glass fibers filled between the plurality of combined wire cores and the mica tape layers; the combined wire core is a mica tape layer, a cross-linked polyethylene layer, and a reinforcement layer wrapped in sequence on the outer surface of the wire core; the component raw materials of the outer sheath are, by mass, 35-45 parts of polyethylene, 21-27 parts of ethylene-vinyl acetate copolymer, 3-8 parts of composite magnesium hydroxide, 7-14 parts of self-healing elastomer, and 1-2 parts of additives.
[0007] Furthermore, the reinforcement layer is one of a glass fiber layer, an aramid fiber layer, a basalt fiber layer, and a carbon fiber layer.
[0008] Furthermore, the auxiliary agent is a defoamer, a leveling agent, and an antioxidant compounded in a mass ratio of 1:1:2.
[0009] Furthermore, the wire core is a copper core.
[0010] Further, the preparation of composite magnesium hydroxide comprises the following steps:
[0011] 1) Mix magnesium hydroxide and deionized water, heat to 60-70°C in a water bath, add sodium oleate, keep warm for 2-3 hours, cool, wash and dry to obtain sodium oleate modified magnesium hydroxide;
[0012] 2) Under a nitrogen atmosphere, sodium oleate-modified magnesium hydroxide, polyvinyl pyrrolidone and ethanol are mixed, and methyl methacrylate, vinyl-terminated branched polycarbosilane and azobisisobutyronitrile are added, and the mixture is kept at 76-80° C. for 5-6 hours, filtered, washed and dried to obtain composite magnesium hydroxide.
[0013] Furthermore, the preparation of the self-healing elastomer comprises the following steps:
[0014] (1) In an ice water bath, vinyl-terminated branched polycarbosilane and tetrahydrofuran are mixed, a mixed solution of m-chloroperbenzoic acid and tetrahydrofuran is added, the temperature is raised to 38-42° C. and kept warm for 10-12 hours, filtered, rinsed with saturated sodium thiosulfate solution, saturated sodium bicarbonate solution, and deionized water for 3-5 times, dried, filtered, rotary evaporated, and dried to obtain epoxidized branched polycarbosilane;
[0015] (2) Mixing the epoxidized branched polycarbosilane and xylene, adding a mixed solution of DOPO and xylene, heating to 138-142°C and keeping the temperature for 10-12 hours, rotary evaporating, vacuum filtering, and drying to obtain a polyhydroxy composite branched polycarbosilane;
[0016] (3) Under a nitrogen atmosphere, polytetrahydrofuran, isophorone diisocyanate, dibutyltin dilaurate and N,N-dimethylacetamide are mixed, the temperature is raised to 73-77°C and kept warm for 2-3 hours, the temperature is lowered to 0°C, a mixed solution of 4,4'-methylenebis(cyclohexylamine) and N,N-dimethylacetamide is added, the temperature is kept warm at 0°C for 5-6 hours, the temperature is raised to 50-60°C, polyhydroxy composite branched polycarbosilane is added, the temperature is kept warm for 2-3 hours, and the material is discharged to obtain a self-healing elastomer.
[0017] Furthermore, the mass ratio of sodium oleate-modified magnesium hydroxide, methyl methacrylate, and vinyl-terminated branched polycarbosilane is 3.2:1:2.4.
[0018] Furthermore, the mass ratio of polytetrahydrofuran, isophorone diisocyanate, 4,4'-methylenebis(cyclohexylamine), and polyhydroxy composite branched polycarbosilane is 6:3.2:1.2:2.
[0019] Further, the preparation of the vinyl terminated branched polycarbosilane comprises the following steps:
[0020] A. Under nitrogen atmosphere, mix magnesium chips, iodine and ether, cool to 0-5°C in an ice bath, add ether and allyl bromide mixed solution, keep warm at 0-5°C for 2h to obtain ether solution of allyl bromide Grignard reagent;
[0021] B. Under nitrogen protection, triallyl (methyl) silane, trichlorosilane, tetrahydrofuran and platinum catalyst are mixed, kept at 58-62°C for 5-6 hours, reduced pressure, anhydrous ether and ether solution of allyl bromide Grignard reagent are added, and stirred at 18-25°C for 10-12 hours to obtain vinyl-terminated branched polycarbosilane.
[0022] Furthermore, a method for preparing a fire-resistant building wire and cable comprises the following steps:
[0023] S1: wrapping the outer surface of the wire core with a mica tape layer, a cross-linked polyethylene layer, and a reinforcement layer in sequence to obtain a combined wire core;
[0024] S2: wrapping a plurality of combined wire cores together with a mica tape layer, and filling the plurality of combined wire cores and the mica tape layer with alkali-free glass fibers to obtain a cable core;
[0025] S3: preparing an outer sheath by blending and extruding polyethylene, ethylene-vinyl acetate copolymer, composite magnesium hydroxide, self-healing elastomer and additives;
[0026] S4: A reinforcement layer and an outer sheath are sequentially coated on the outer surface of the cable core to obtain a fire-resistant building wire and cable.
[0027] Beneficial effects of the present invention:
[0028] The invention provides a fire-resistant building wire and cable and a preparation method thereof. Through process and component design, a flame-retardant, waterproof and mechanical damage-resistant fire-resistant building wire and cable is prepared.
[0029] In order to improve the mechanical properties and fire resistance of the wire and cable, the present invention wraps a mica tape, a cross-linked polyethylene insulation layer, and a tear-resistant fiber reinforcement layer on the outer surface of a copper core to form an oxygen insulation layer of a combined core, and multiple combined cores are wrapped together with a mica tape layer, and flame-retardant filler alkali-free glass fiber is filled in the multiple combined cores and the mica tape layer to obtain a cable core, and then the tear-resistant fiber reinforcement layer and a low-smoke halogen-free flame-retardant outer sheath with self-healing ability are sequentially coated on the outside of the cable core, thereby improving the impact resistance, spray resistance, high temperature resistance, and ablation resistance of the wire and cable.
[0030] In the present invention, green and environmentally friendly flame retardant magnesium hydroxide is selected as the flame retardant filler of the outer sheath. In order to improve the problems of low flame retardant efficiency, large addition amount, poor compatibility and the like when single magnesium hydroxide is added, the present invention performs modification treatment on the magnesium hydroxide, and improves the uniformity of its dispersion in the outer sheath base material at the same time. Sodium oleate is used to perform surface chemical coating modification on the magnesium hydroxide, so that the hydrophilicity of the magnesium hydroxide is changed to hydrophobicity, and carbon-carbon double bonds are introduced on the surface. Under the action of an initiator, the unsaturated double bonds are opened and polymerized with methyl methacrylate and vinyl-terminated branched polycarbosilane to obtain flame retardant and hydrophobic composite magnesium hydroxide; wherein the vinyl-terminated branched polycarbosilane is obtained by reacting cheap and readily available methyltrichlorosilane with an allyl bromide Grignard reagent, and has the advantages of being cross-linked during pyrolysis, organic-inorganic conversion, good thermal stability, and promoting carbonization, so as to synergize the flame retardancy, fire resistance and smoke suppression of the magnesium hydroxide.
[0031] In order to give the outer sheath excellent resistance to mechanical damage, a self-healing flame-retardant elastomer is introduced into the outer sheath. Polytetrahydrofuran, isophorone diisocyanate, and 4.4'-methylenebis(cyclohexylamine) are used as raw materials, and polyhydroxy composite branched polycarbosilane is used as a capping agent. By regulating the multi-level hydrogen bond interaction between molecules, a polyurea-polyurethane elastomer with high toughness, high mechanical strength and excellent self-healing efficiency is prepared; wherein the polyhydroxy composite branched polycarbosilane is prepared by oxidizing part of the double bonds of the vinyl-terminated branched polycarbosilane to epoxy bonds with meta-chloroperbenzoic acid, and then utilizing the PH bond of DOPO to react with the epoxy bond to graft DOPO to obtain polyhydroxy composite branched polycarbosilane, thereby giving the self-healing elastomer excellent flame retardancy, achieving a long-lasting flame retardant effect, and greatly extending the service life of wires and cables. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.
[0034] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0035] Embodiment 1: A method for preparing fire-resistant building wire and cable, comprising the following steps:
[0036] S1: wrapping the outer surface of the wire core with a mica tape layer, a cross-linked polyethylene layer, and a reinforcement layer in sequence to obtain a combined wire core;
[0037] The wire core is a copper core; the reinforcement layer is a glass fiber cloth layer;
[0038] S2: wrapping a plurality of combined wire cores together with a mica tape layer, and filling the plurality of combined wire cores and the mica tape layer with alkali-free glass fibers to obtain a cable core;
[0039] S3: preparing an outer sheath by blending and extruding polyethylene, ethylene-vinyl acetate copolymer, composite magnesium hydroxide, self-healing elastomer and additives;
[0040] In terms of mass, the raw materials of the outer sheath are: 35 parts of polyethylene, 21 parts of ethylene-vinyl acetate copolymer, 3 parts of composite magnesium hydroxide, 7 parts of self-healing elastomer, and 1 part of additive;
[0041] The auxiliary agent is a defoamer, a leveling agent, and an antioxidant mixed in a mass ratio of 1:1:2;
[0042] The preparation of composite magnesium hydroxide comprises the following steps:
[0043] 1) Mix 5 g of magnesium hydroxide and 160 mL of deionized water, heat to 60 ° C in a water bath, add 0.15 g of sodium oleate, keep warm for 2 hours, cool, wash and dry to obtain sodium oleate modified magnesium hydroxide;
[0044] 2) Under nitrogen atmosphere, 3.2 g of sodium oleate-modified magnesium hydroxide, 0.4 g of polyvinyl pyrrolidone, and 100 mL of ethanol were mixed, and 1 g of methyl methacrylate, 2.4 g of vinyl-terminated branched polycarbosilane, and 0.2 g of azobisisobutyronitrile were added, and the mixture was kept at 76 ° C for 6 h, filtered, washed, and dried to obtain composite magnesium hydroxide;
[0045] The preparation of the self-healing elastomer includes the following steps:
[0046] (1) In an ice water bath, 6.2 g of vinyl-terminated branched polycarbosilane and 44 mL of tetrahydrofuran were mixed, and a mixture of 5.6 g of m-chloroperbenzoic acid and 44 mL of tetrahydrofuran was added, and the mixture was heated to 38° C. and kept warm for 12 h. The mixture was filtered, and rinsed with saturated sodium thiosulfate solution, saturated sodium bicarbonate solution, and deionized water for three times in sequence, dried, filtered, rotary evaporated, and dried to obtain epoxidized branched polycarbosilane;
[0047] (2) 3.4 g of epoxidized branched polycarbosilane and 300 mL of xylene were mixed, and a mixture of 2.2 g of DOPO and 100 mL of xylene was added, and the mixture was heated to 138° C. and kept warm for 12 h, and then rotary evaporated, filtered under reduced pressure, and dried to obtain a polyhydroxy composite branched polycarbosilane;
[0048] (3) Under a nitrogen atmosphere, 6 g of polytetrahydrofuran, 3.2 g of isophorone diisocyanate, 15 µL of dibutyltin dilaurate, and 15 mL of N,N-dimethylacetamide were mixed, heated to 73 °C and kept warm for 3 h, cooled to 0 °C, and a mixture of 1.2 g of 4,4'-methylenebis(cyclohexylamine) and 20 mL of N,N-dimethylacetamide was added, and kept warm at 0 °C for 5 h, heated to 50 °C, and 2 g of polyhydroxy composite branched polycarbosilane was added, and kept warm for 2 h, and the self-healing elastomer was obtained;
[0049] The preparation of vinyl terminated branched polycarbosilane comprises the following steps:
[0050] A. Under nitrogen atmosphere, mix 3g magnesium chips, 0.05g iodine, and 50mL ether, cool to 0℃ in an ice bath, add 20mL ether and 12.6g allyl bromide mixed solution, and keep at 0℃ for 2h to obtain an ether solution of allyl bromide Grignard reagent;
[0051] B. Under nitrogen protection, 1.6 g of triallyl (methyl) silane, 7.2 g of trichlorosilane, 60 mL of tetrahydrofuran, and 0.2 μL of platinum catalyst were mixed, kept at 58°C for 6 h, decompressed, 20 mL of anhydrous ether was added, and an ether solution of allyl bromide Grignard reagent was added, and stirred at 18°C for 12 h to obtain vinyl-terminated branched polycarbosilane;
[0052] S4: A reinforcement layer and an outer sheath are sequentially coated on the outer surface of the cable core to obtain a fire-resistant building wire and cable.
[0053] Embodiment 2: A method for preparing fire-resistant building wire and cable, comprising the following steps:
[0054] S1: wrapping the outer surface of the wire core with a mica tape layer, a cross-linked polyethylene layer, and a reinforcement layer in sequence to obtain a combined wire core;
[0055] The wire core is a copper core; the reinforcement layer is a glass fiber cloth layer;
[0056] S2: wrapping a plurality of combined wire cores together with a mica tape layer, and filling the plurality of combined wire cores and the mica tape layer with alkali-free glass fibers to obtain a cable core;
[0057] S3: preparing an outer sheath by blending and extruding polyethylene, ethylene-vinyl acetate copolymer, composite magnesium hydroxide, self-healing elastomer and additives;
[0058] In terms of mass, the components of the outer sheath are: 39 parts of polyethylene, 25 parts of ethylene-vinyl acetate copolymer, 5 parts of composite magnesium hydroxide, 12 parts of self-healing elastomer, and 1.5 parts of additives;
[0059] The auxiliary agent is a defoamer, a leveling agent, and an antioxidant mixed in a mass ratio of 1:1:2;
[0060] The preparation of composite magnesium hydroxide comprises the following steps:
[0061] 1) Mix 5 g of magnesium hydroxide and 160 mL of deionized water, heat to 65 ° C in a water bath, add 0.15 g of sodium oleate, keep warm for 2.5 hours, cool, wash and dry to obtain sodium oleate modified magnesium hydroxide;
[0062] 2) Under a nitrogen atmosphere, 3.2 g of sodium oleate-modified magnesium hydroxide, 0.4 g of polyvinyl pyrrolidone, and 100 mL of ethanol were mixed, and 1 g of methyl methacrylate, 2.4 g of vinyl-terminated branched polycarbosilane, and 0.2 g of azobisisobutyronitrile were added, and the mixture was kept at 78° C. for 5.5 h, filtered, washed, and dried to obtain composite magnesium hydroxide;
[0063] The preparation of the self-healing elastomer includes the following steps:
[0064] (1) In an ice water bath, 6.2 g of vinyl-terminated branched polycarbosilane and 44 mL of tetrahydrofuran were mixed, and a mixture of 5.6 g of m-chloroperbenzoic acid and 44 mL of tetrahydrofuran was added, and the mixture was heated to 40° C. and kept warm for 11 h. The mixture was filtered and rinsed four times with saturated sodium thiosulfate solution, saturated sodium bicarbonate solution, and deionized water, respectively, and dried, filtered, rotary evaporated, and dried to obtain epoxidized branched polycarbosilane;
[0065] (2) 3.4 g of epoxidized branched polycarbosilane and 300 mL of xylene were mixed, and a mixture of 2.2 g of DOPO and 100 mL of xylene was added, and the mixture was heated to 140° C. and kept warm for 11 h, and then rotary evaporated, filtered under reduced pressure, and dried to obtain a polyhydroxy composite branched polycarbosilane;
[0066] (3) Under a nitrogen atmosphere, 6 g of polytetrahydrofuran, 3.2 g of isophorone diisocyanate, 15 µL of dibutyltin dilaurate, and 15 mL of N,N-dimethylacetamide were mixed, heated to 75 °C and kept warm for 2.5 h, cooled to 0 °C, and a mixture of 1.2 g of 4,4'-methylenebis(cyclohexylamine) and 20 mL of N,N-dimethylacetamide was added, and kept warm at 0 °C for 5.5 h, heated to 55 °C, and 2 g of polyhydroxy composite branched polycarbosilane was added, and kept warm for 2.5 h, and the self-healing elastomer was obtained;
[0067] The preparation of vinyl terminated branched polycarbosilane comprises the following steps:
[0068] A. Under nitrogen atmosphere, mix 3g magnesium chips, 0.05g iodine, and 50mL ether, cool to 3°C in an ice bath, add 20mL ether and 12.6g allyl bromide mixed solution, and keep warm at 3°C for 2h to obtain an ether solution of allyl bromide Grignard reagent;
[0069] B. Under nitrogen protection, 1.6 g of triallyl (methyl) silane, 7.2 g of trichlorosilane, 60 mL of tetrahydrofuran, and 0.2 μL of platinum catalyst were mixed, kept at 60°C for 5.5 h, decompressed, 20 mL of anhydrous ether was added, and an ether solution of allyl bromide Grignard reagent was added, and stirred at 20°C for 11 h to obtain vinyl-terminated branched polycarbosilane;
[0070] S4: A reinforcement layer and an outer sheath are sequentially coated on the outer surface of the cable core to obtain a fire-resistant building wire and cable.
[0071] Embodiment 3: A method for preparing fire-resistant building wire and cable, comprising the following steps:
[0072] S1: wrapping the outer surface of the wire core with a mica tape layer, a cross-linked polyethylene layer, and a reinforcement layer in sequence to obtain a combined wire core;
[0073] The wire core is a copper core; the reinforcement layer is a glass fiber cloth layer;
[0074] S2: wrapping a plurality of combined wire cores together with a mica tape layer, and filling the plurality of combined wire cores and the mica tape layer with alkali-free glass fibers to obtain a cable core;
[0075] S3: preparing an outer sheath by blending and extruding polyethylene, ethylene-vinyl acetate copolymer, composite magnesium hydroxide, self-healing elastomer and additives;
[0076] In terms of mass, the components of the outer sheath are: 45 parts of polyethylene, 27 parts of ethylene-vinyl acetate copolymer, 8 parts of composite magnesium hydroxide, 14 parts of self-healing elastomer, and 2 parts of additives;
[0077] The auxiliary agent is a defoamer, a leveling agent, and an antioxidant mixed in a mass ratio of 1:1:2;
[0078] The preparation of composite magnesium hydroxide comprises the following steps:
[0079] 1) Mix 5 g of magnesium hydroxide and 160 mL of deionized water, heat to 70 ° C in a water bath, add 0.15 g of sodium oleate, keep warm for 3 hours, cool, wash and dry to obtain sodium oleate modified magnesium hydroxide;
[0080] 2) Under a nitrogen atmosphere, 3.2 g of sodium oleate-modified magnesium hydroxide, 0.4 g of polyvinyl pyrrolidone, and 100 mL of ethanol were mixed, and 1 g of methyl methacrylate, 2.4 g of vinyl-terminated branched polycarbosilane, and 0.2 g of azobisisobutyronitrile were added, and the mixture was kept at 80° C. for 5 h, filtered, washed, and dried to obtain composite magnesium hydroxide;
[0081] The preparation of the self-healing elastomer includes the following steps:
[0082] (1) In an ice water bath, 6.2 g of vinyl-terminated branched polycarbosilane and 44 mL of tetrahydrofuran were mixed, and a mixture of 5.6 g of m-chloroperbenzoic acid and 44 mL of tetrahydrofuran was added, and the mixture was heated to 42° C. and kept warm for 10 h. The mixture was filtered and rinsed with saturated sodium thiosulfate solution, saturated sodium bicarbonate solution, and deionized water for 5 times in sequence, dried, filtered, rotary evaporated, and dried to obtain epoxidized branched polycarbosilane;
[0083] (2) 3.4 g of epoxidized branched polycarbosilane and 300 mL of xylene were mixed, and a mixture of 2.2 g of DOPO and 100 mL of xylene was added, and the mixture was heated to 142° C. and kept warm for 10 h, and then rotary evaporated, filtered under reduced pressure, and dried to obtain a polyhydroxy composite branched polycarbosilane;
[0084] (3) Under a nitrogen atmosphere, 6 g of polytetrahydrofuran, 3.2 g of isophorone diisocyanate, 15 µL of dibutyltin dilaurate, and 15 mL of N,N-dimethylacetamide were mixed, heated to 77 °C and kept warm for 2 h, cooled to 0 °C, and a mixture of 1.2 g of 4,4'-methylenebis(cyclohexylamine) and 20 mL of N,N-dimethylacetamide was added, and kept warm at 0 °C for 6 h, heated to 60 °C, and 2 g of polyhydroxy composite branched polycarbosilane was added, and kept warm for 2 h, and the mixture was discharged to obtain a self-healing elastomer;
[0085] The preparation of vinyl terminated branched polycarbosilane comprises the following steps:
[0086] A. Under nitrogen atmosphere, mix 3g magnesium chips, 0.05g iodine, and 50mL ether, cool to 5°C in an ice bath, add 20mL ether and 12.6g allyl bromide mixed solution, and keep at 5°C for 2h to obtain an ether solution of allyl bromide Grignard reagent;
[0087] B. Under nitrogen protection, 1.6 g of triallyl (methyl) silane, 7.2 g of trichlorosilane, 60 mL of tetrahydrofuran, and 0.2 μL of platinum catalyst were mixed, kept at 62°C for 5 h, decompressed, 20 mL of anhydrous ether was added, and an ether solution of allyl bromide Grignard reagent was added, and stirred at 25°C for 10 h to obtain vinyl-terminated branched polycarbosilane;
[0088] S4: A reinforcement layer and an outer sheath are sequentially coated on the outer surface of the cable core to obtain a fire-resistant building wire and cable.
[0089] Comparative Example 1: Taking Example 3 as the control group, magnesium hydroxide was used to replace the composite magnesium hydroxide, and other processes were normal.
[0090] Comparative Example 2: Taking Example 3 as the control group, in the preparation of the self-healing elastomer, no polyhydroxy composite branched polycarbosilane was added, and other processes were normal.
[0091] Comparative Example 3: Example 3 was used as the control group, vinyl-terminated branched polycarbosilane was not prepared, and other processes were normal.
[0092] In the embodiment and the comparative example, the cable core contains 5 combined wire cores, the thickness of the cross-linked polyethylene layer and the reinforcement layer is 2 mm, and the thickness of the outer sheath is 2 mm.
[0093] The preparation of the cross-linked polyethylene layer in the embodiments and comparative examples comprises the following steps:
[0094] 0.5 g of BHT antioxidant was mixed with 100 g of polyethylene (2426H) using a high-speed mixer, extruded into granules, and then transferred to an internal mixer, 0.2 g of di(hexadecyl) peroxide dicarbonate was added, and internal mixing was performed for 20 min. The mixture was formed and pressed on a tablet press at 130 ° C, and then cross-linked at 180 ° C for 10 min to obtain a cross-linked polyethylene layer.
[0095] Source of raw materials (for demonstration only):
[0096] Mica tape (single-sided gold mica tape, thickness of 0.14mm): Changzhou Zhongnan Electronic Technology Co., Ltd.; Hexadecyl peroxide dicarbonate 26322-14-5: Hubei Rishengchang New Material Technology Co., Ltd.; Glass fiber cloth EW250F (0.25mm): Sinoma Science and Technology Co., Ltd.; Alkali-free glass fiber (industrial grade): Hubei Chengfeng Chemical Co., Ltd.; Polyethylene (2426H): CNOOC Shell Petrochemical Co., Ltd.; Ethylene-vinyl acetate copolymer 24937-78-8: Hubei Yongkuo Technology Co., Ltd.; Leveling agent ET10, defoaming agent M101: Shandong Dayi Chemical Co., Ltd.; BHT antioxidant 360: EVA DuPont; Magnesium hydroxide A00414: Wuhan Jiyesheng Chemical Co., Ltd.; Allyl bromide 106-95-6: Zouping Mingxing Chemical Co., Ltd.; Trichlorosilane 10025-78-2: Wuhan Kanos Technology Co., Ltd. Company; sodium oleate S104195, polyvinyl pyrrolidone P434440, methyl methacrylate M109623, azobisisobutyronitrile A434183, tetrahydrofuran T431413, m-chloroperbenzoic acid C106492, sodium thiosulfate S433978, DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) D102416, polytetrahydrofuran P118599, isoflurane Ketone diisocyanate I109582, dibutyltin dilaurate D100274, N,N-dimethylacetamide D108096, 4,4'-methylenebis(cyclohexylamine) M158600, magnesium chips M109154, iodine I116350, triallyl(methyl)silane T162542, platinum catalyst P141457: Aladdin reagent; ethanol, sodium bicarbonate, xylene, ether, analytical grade: Sinopharm reagent.
[0097] Performance test: The outer sheaths prepared in the embodiments and comparative examples were subjected to performance tests:
[0098] Flame retardant grade: Refer to GB / T2408-2008 to determine the vertical combustion grade of the sample, the sample size is 120mm long and 20mm wide; Self-healing rate: Make an initial scratch on the surface with a length of 1mm, a width of 2µm, and a depth of 1mm, keep it at 80℃ for 12h, and observe the existing scratch length with an electron microscope. The self-healing rate = (L 初始划痕长度 -L 现有划痕长度 ) / L 初始划痕长度 ×100%; Water resistance: put the outer sheath into 5g / L sodium chloride solution and soak it at 30℃ for 15 days. If there is no blistering or damage on the surface, it is excellent, otherwise it is unqualified. The test results are shown in Table 1 below;
[0099]
[0100] The present invention provides a fire-resistant building wire and cable and a preparation method thereof. Through process and component design, a flame-retardant, waterproof and mechanically damage-resistant fire-resistant building wire and cable is prepared. In Table 1, / indicates that the item has not been tested.
[0101] Example 3 is compared with Comparative Example 1 and Comparative Example 3. In the present invention, green and environmentally friendly flame retardant magnesium hydroxide is selected as the flame retardant filler of the outer sheath. In order to improve the problems of low flame retardant efficiency, large addition amount, poor compatibility, etc. when a single magnesium hydroxide is added, the present invention performs a modification treatment on the magnesium hydroxide, and at the same time improves its uniformity of dispersion in the outer sheath base material. Sodium oleate is used to perform surface chemical coating modification on the magnesium hydroxide, so that the magnesium hydroxide changes from hydrophilic to hydrophobic, and introduces carbon-carbon double bonds on the surface. Under the action of an initiator, the unsaturated double bonds are opened and polymerized with methyl methacrylate and vinyl-terminated branched polycarbosilane to obtain a flame retardant and hydrophobic composite magnesium hydroxide; wherein the vinyl-terminated branched polycarbosilane is obtained by reacting cheap and readily available methyltrichlorosilane with an allyl bromide Grignard reagent, and can undergo cross-linking, organic-inorganic conversion, good thermal stability, and promote carbonization during its pyrolysis process, thereby synergizing the flame retardancy, fire resistance, and smoke suppression of the magnesium hydroxide.
[0102] Example 3 is compared with Comparative Examples 2 and 3. In order to give the outer sheath excellent resistance to mechanical damage, a self-healing flame-retardant elastomer is introduced into the outer sheath. Polytetrahydrofuran, isophorone diisocyanate, and 4.4'-methylenebis(cyclohexylamine) are used as raw materials, and polyhydroxy composite branched polycarbosilane is used as a capping agent. By regulating the multi-level hydrogen bond interaction between molecules, a polyurea-polyurethane elastomer with high toughness, high mechanical strength and excellent self-healing efficiency is prepared; wherein the polyhydroxy composite branched polycarbosilane is obtained by oxidizing part of the double bonds of the vinyl-terminated branched polycarbosilane with meta-chloroperbenzoic acid to epoxy bonds, and then utilizing the PH bond of DOPO to react with the epoxy bond to graft DOPO to obtain polyhydroxy composite branched polycarbosilane, which gives the self-healing elastomer excellent flame retardancy and achieves a long-lasting flame retardant effect, thereby greatly extending the service life of the wire and cable.
[0103] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A fire-resistant building wire and cable, characterized in that: It comprises a cable core, a reinforcement layer wrapped on the surface of the cable core, and an outer sheath; the cable core is composed of a plurality of combined wire cores, a mica tape layer wrapped on the plurality of combined wire cores, and an alkali-free glass fiber filled between the plurality of combined wire cores and the mica tape layer; the combined wire core is a mica tape layer, a cross-linked polyethylene layer, and a reinforcement layer wrapped in sequence on the outer surface of the wire core; the component raw materials of the outer sheath are, by weight: 35-45 parts of polyethylene, 21-27 parts of ethylene-vinyl acetate copolymer, 3-8 parts of composite magnesium hydroxide, 7-14 parts of self-healing elastomer, and 1-2 parts of additives; The preparation of the composite magnesium hydroxide comprises the following steps: 1) Mix magnesium hydroxide and deionized water, heat to 60-70°C in a water bath, add sodium oleate, keep warm for 2-3 hours, cool, wash and dry to obtain sodium oleate modified magnesium hydroxide; 2) Under a nitrogen atmosphere, sodium oleate-modified magnesium hydroxide, polyvinyl pyrrolidone, and ethanol are mixed, and methyl methacrylate, vinyl-terminated branched polycarbosilane, and azobisisobutyronitrile are added, and the mixture is kept at 76-80° C. for 5-6 hours, filtered, washed, and dried to obtain composite magnesium hydroxide; The preparation of the self-healing elastomer comprises the following steps: (1) In an ice water bath, vinyl-terminated branched polycarbosilane and tetrahydrofuran are mixed, a mixed solution of m-chloroperbenzoic acid and tetrahydrofuran is added, the temperature is raised to 38-42° C. and kept warm for 10-12 hours, filtered, rinsed with saturated sodium thiosulfate solution, saturated sodium bicarbonate solution, and deionized water for 3-5 times, dried, filtered, rotary evaporated, and dried to obtain epoxidized branched polycarbosilane; (2) Mixing the epoxidized branched polycarbosilane and xylene, adding a mixed solution of DOPO and xylene, heating to 138-142°C and keeping the temperature for 10-12 hours, rotary evaporating, vacuum filtering, and drying to obtain a polyhydroxy composite branched polycarbosilane; (3) In a nitrogen atmosphere, polytetrahydrofuran, isophorone diisocyanate, dibutyltin dilaurate, and N,N-dimethylacetamide are mixed, heated to 73-77°C and kept warm for 2-3 hours, cooled to 0°C, a mixed solution of 4,4'-methylenebis(cyclohexylamine) and N,N-dimethylacetamide is added, kept warm at 0°C for 5-6 hours, heated to 50-60°C, polyhydroxy composite branched polycarbosilane is added, kept warm for 2-3 hours, and discharged to obtain a self-healing elastomer; The preparation of vinyl terminated branched polycarbosilane comprises the following steps: A. Under nitrogen atmosphere, mix magnesium chips, iodine and ether, cool to 0-5°C in an ice bath, add ether and allyl bromide mixed solution, keep warm at 0-5°C for 2h to obtain ether solution of allyl bromide Grignard reagent; B. Under nitrogen protection, triallyl (methyl) silane, trichlorosilane, tetrahydrofuran and platinum catalyst are mixed, kept at 58-62°C for 5-6 hours, reduced pressure, anhydrous ether and ether solution of allyl bromide Grignard reagent are added, and stirred at 18-25°C for 10-12 hours to obtain vinyl-terminated branched polycarbosilane.
2. A fire-resistant building wire and cable according to claim 1, characterized in that: The reinforcement layer is one of a glass fiber layer, an aramid fiber layer, a basalt fiber layer, and a carbon fiber layer.
3. A fire-resistant building wire and cable according to claim 1, characterized in that: The auxiliary agent is a defoamer, a leveling agent and an antioxidant mixed in a mass ratio of 1:1:
2.
4. A fire-resistant building wire and cable according to claim 1, characterized in that: The wire core is a copper core.
5. The fire-resistant building wire and cable according to claim 1, characterized in that: In the preparation of composite magnesium hydroxide, the mass ratio of sodium oleate modified magnesium hydroxide, methyl methacrylate and vinyl terminated branched polycarbosilane is 3.2:1:2.
4.
6. The fire-resistant building wire and cable according to claim 1, characterized in that: In the preparation of the self-healing elastomer, the mass ratio of polytetrahydrofuran, isophorone diisocyanate, 4,4'-methylenebis(cyclohexylamine), and polyhydroxy composite branched polycarbosilane is 6:3.2:1.2:
2.
7. A method for preparing a fire-resistant building wire and cable according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: wrapping the outer surface of the wire core with a mica tape layer, a cross-linked polyethylene layer, and a reinforcement layer in sequence to obtain a combined wire core; S2: wrapping a plurality of combined wire cores together with a mica tape layer, and filling the plurality of combined wire cores and the mica tape layer with alkali-free glass fibers to obtain a cable core; S3: preparing an outer sheath by blending and extruding polyethylene, ethylene-vinyl acetate copolymer, composite magnesium hydroxide, self-healing elastomer and additives; S4: A reinforcement layer and an outer sheath are sequentially coated on the outer surface of the cable core to obtain a fire-resistant building wire and cable.
Citation Information
Patent Citations
High-performance flame-retardant low-smoke optical cable for rail transit
CN115755298A
Novel high fire -retardant fireproof control cable
CN208111116U